2012
DOI: 10.1002/app.37520
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis and characterization of poly(HEMA‐co‐MMA)‐g‐POSS nanocomposites by combination of reversible addition fragmentation chain transfer polymerization and click chemistry

Abstract: New hybrid poly(hydroxyethyl methacrylate-co-methyl methacrylate)-g-polyhedral oligosilsesquioxane [poly(HEMA-co-MMA)-g-POSS] nanocomposites were synthesized by the combination of reversible addition fragmentation chain transfer (RAFT) polymerization and click chemistry using a grafting to protocol. Initially, the random copolymer poly(HEMA-co-MMA) was prepared by RAFT polymerization of HEMA and MMA. Alkynyl side groups were introduced onto the polymeric backbones by esterification reaction between 4-pentynoic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
9
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 25 publications
(9 citation statements)
references
References 44 publications
0
9
0
Order By: Relevance
“…As an example, mono azide functional POSS was synthesized and used in fabrication of poly( N -isopropyl acrylamide)-based thermoresponsive nanocomposite hydrogels [ 34 ]. Thermally curable polybenzoxazine nanocomposite of multi-azide functional POSS [ 35 ], star and network polymers [ 36 , 37 , 38 ], linear polypeptide [ 39 ] and poly(HEMA- co -MMA)-based nanocomposites of mono-azide functional POSS [ 40 ] were also fabricated through CuAAC click methodology.…”
Section: Click Chemistry-based Methodologies In Polymer Nanocomposmentioning
confidence: 99%
“…As an example, mono azide functional POSS was synthesized and used in fabrication of poly( N -isopropyl acrylamide)-based thermoresponsive nanocomposite hydrogels [ 34 ]. Thermally curable polybenzoxazine nanocomposite of multi-azide functional POSS [ 35 ], star and network polymers [ 36 , 37 , 38 ], linear polypeptide [ 39 ] and poly(HEMA- co -MMA)-based nanocomposites of mono-azide functional POSS [ 40 ] were also fabricated through CuAAC click methodology.…”
Section: Click Chemistry-based Methodologies In Polymer Nanocomposmentioning
confidence: 99%
“…Azide–alkyne cycloaddition can also be used for the preparation of nanocomposites. Islam et al [ 208 ] synthesized a random copolymer of methyl methacrylate and 2-hydroxyethyl methacrylate (70/30 vol.) with M n = 16 kg⋅mol − 1 and Ð = 1.61 in the presence of 2-cyano-2-propyl dodecyl trithiocarbonate as a RAFT agent.…”
Section: Post-modification Of Side-group Approachmentioning
confidence: 99%
“…Laine et al [25] reported the POSS with average of four LC motifs in each molecule, which has only nematic phase. An LC material with both nematic and smectic crystalline phases containing an average of five LC elements in the molecule was prepared by controlling the feed ratio [26]. The incorporation of POSS into LCP increased the liquid phase transition temperature and enriched the LC phase.…”
Section: Introductionmentioning
confidence: 99%